Films about the deaf: the representations of deaf and sign languages (Práxis Educativa, 2009)
This paper analyzes two films about deafness which have not been investigated in the Brazilian academic context. They are Mandy (directed by Alexander Mackendrick, 1952, England) and After the Silence (by Fred Gerber, 1996, USA). The analysis is supported by Cultural Studies and Deaf Studies, especially on the concepts of cultural pedagogies, deaf culture, deaf identities, sign language, as well as on the analysis of other films about deaf people conducted by Thoma (2004). Both films are classified as drama, and particular attention was given to how deaf characters are represented, highlighting scenes showing the difficulties deaf people face in a hearing society. It is worth noting that in the end of both films the deaf characters manage to speak and hear. The pedagogical impact of these films is questioned as they show that the deaf may be able to speak and hear after using Sign Language. Deaf representations, deaf education and sign language are present in both films, although there is a difference in approach between them. Keywords: Films. Education of deaf people. Sign Language.